Moist Convection Is Most Vigorous at Intermediate Atmospheric Humidity - Jacob T. Seeley; Robin D. Wordsworth (The Planetary Science Journal, 2023)
In Earth’s current climate, moist convective updraft speeds increase with surface warming. This trend suggests that very vigorous convection might be the norm in extremely hot and humid atmospheres, such as those undergoing a runaway greenhouse transition. However, theoretical and numerical evidence suggests that convection is actually gentle in water-vapor-dominated atmospheres, implying that convective vigor may peak at some intermediate humidity level. Here, we perform small-domain convection-resolving simulations of an Earth-like atmosphere over a wide range of surface temperatures and confirm that there is indeed a peak in convective vigor, which we show occurs near T _s ≃ 330 K. We show that a similar peak in convective vigor exists when the relative abundance of water vapor is changed by varying the amount of background (noncondensing) gas at fixed T _s , which may have implications for Earth’s climate and atmospheric chemistry during the Hadean and Archean eons. We also show that Titan-like thermodynamics (i.e., a thick nitrogen atmosphere with condensing methane and low gravity) produce a peak in convective vigor at T _s ≃ 95 K, which is curiously close to the current surface temperature of Titan. Plotted as functions of the saturation-specific humidity at cloud base, metrics of convective vigor from both Earth-like and Titan-like experiments all peak when cloud-base air contains roughly 10% of the condensible gas by mass. Our results point to a potentially common phenomenon in terrestrial atmospheres: that moist convection is most vigorous when the condensible component is between dilute and nondilute abundance.